An introduction to mathematics for economics - Asano, Akihito, 1972- (2013)
"An Introduction to Mathematics for Economics introduces quantitative methods to students of economics and finance in a succinct and accessible style. The introductory nature of this textbook means a background in economics is not essential, as it aims to help students appreciate that learning mathematics is relevant to their overall understanding of the subject. Economic and financial applications are explained in detail before students learn how mathematics can be used, enabling students to learn how to put mathematics into practice. Starting with a revision of basic mathematical principles the second half of the book introduces calculus, emphasising economic applications throughout. Appendices on matrix algebra and difference/differential equations are included for the benefit of more advanced students. Other features, including worked examples and exercises, help to underpin the readers' knowledge and learning. Akihito Asano has drawn upon his own extensive teaching experience to create an unintimidating yet rigorous textbook"--
Machine generated contents note: 1. Demand and supply in competitive markets; 2. Basic mathematics; 3. Financial mathematics; 4. Differential calculus I; 5. Differential calculus II; 6. Multivariate calculus; 7. Integral calculus; Appendix A. Matrix algebra; Appendix B. An introduction to difference and differential equations.
Includes index.
Includes bibliographical references and index.
Keywords: Business mathematics; Business -- Mathematical models; BUSINESS & ECONOMICS / Econometrics